INTEGRASI NILAI SYARIAH DALAM GIG ECONOMY: REFLEKSI ATAS ETIKA KERJA, MANAJEMEN ALGORITMIK, DAN TATA KELOLA DI INDONESIA - Rizqi Anfanni Fahmi (Jurnal Ekshis, 2025)
This study explores the intersection of the Gig Economy, algorithmic management, and Islamic work ethics within Indonesia’s halal economy governance. Using a narrative review approach based on the Scopus database with the Boolean string “GIG ECONOMY” AND “HALAL INDUSTRY,” it synthesizes multidisciplinary literature to evaluate how digital efficiency aligns with maqāṣid al-sharīʿah principles. Findings indicate hat while the platform economy expands employment opportunities, it also generates ethical challenges regarding worker autonomy, algorithmic transparency, and fair remuneration. Algorithmic control often contradicts Islamic values of ‘adl (justice), amanah (trust), and maslahah (public welfare). The study proposes sharia-based governance, Islamic social protection instruments, and blockchain-enabled algorithmic audits to enhance ethical digital labor systems. Contributing to the integration of Islamic ethics and digital governance, this research underscores the need for future empirical studies to develop measurable indicators of sharia-based algorithmic fairness for global application.